Company income tax revenue and economic growth: empirical evidence from Sub-Sahara countries in Africa (Journal of Economic Research & Business Administration, 2022)
The development level of any country depends on the volume of revenue realised for the infrastructureprovisions. For decades ago, local resource mobilization issue has enticed significant attention inSub-Sahara countries in Africa due to paucity of income generated. The aim of this study is to examinethe effect of CIT revenue on the growth of Sub-Sahara counties in Africa. Data from ten Sub-Saharacountries which comprised of Nigeria, Liberia, Sierra Leon, Ghana, South Africa, Senegal, Benin, Burkina-Faso, Guinea and Mali were employed from year 2000 to 2019. However, the data were sourcedmajorly from World Development Indicator (WDI) and analyzed using Panel data analysis and ARDL.Based on our findings, the Coefficients of all the variables, especially CIT are negative and insignificant,this goes to validate the speed of adjustment of 1.8% (coefficient of -1.86124), meaning that 1% changein CIT absolutely bring down GDP by 1.8% in the long run but in the short run, 1% change in CIT logicallybring down GDP by 0.5% (coefficient of 0.596384). Conclusively, company income tax revenuenegatively affected the growth of Sub-Sahara countries in Africa over the period of study both in the shortand long run. It is recommended that fiscal authorities of respective countries should create databasemechanism which will expose annual chargeable profit and tax payable for each company in order toeschew CIT evasion in the country. Regulatory authorities saddled with the monopolistic responsibilityof tax collection should be empowered to impose compliance on CIT payers which will upsurge CITrevenue enormously. Lastly, CIT tax collected should be appropriately dispersed to breed growth ofeconomy for effective compliance of taxpayers.Key words: Sub-Sahara, Countries, CIT, Growth, ARDL, Revenue.